In vitro antimicrobial study of new modifications of Salvia officinalis extracts - Verkhovodovoda, Y; Kireyev, I; Koshovyi, O; Osolodchenko, T (Annals of Mechnikov's Institute, 2019)
Indroduction. During treatment with antibiotics and up to 12 weeks after its completion, in 5-30 % of patients antibiotic-associated diarrhea is recorded. It arises in connection with the treatment of antibiotics, without other obvious causes, including acute violation of normal intestinal flora. The most common cause of antibiotic-associated diarrhea among children and adults is Clostridium difficile. C. difficile infection is associated with significant morbidity and mortality. In the case of clostridial infection, antibacterial therapy with metronidazole, vancomycin, rifaximin, fidaksomycin, which has a number of side effects; there is also a fact of development of microorganism resistance. Actual issue of pharmacy is a development of a safe plant antimicrobial agent. Materials and methods. Extracts were obtained at the Department of Pharmacognosy of the National University of Pharmacy (Kharkiv, Ukraine) and provided for study. The antimicrobial activity of derivatives of salivary grass extracts was determined in the Laboratory of Biochemistry and Biotechnology of the Mechnikov Institute of Microbiology and Immunology (Kharkiv, Ukraine) in vitro experiment using the method of diffusion in agar - "the method of wells", which is based on the ability of the active substance to diffuse into agar with a standard test culture. The results obtained with this method allow characterizing the antimicrobial activity of the test sample, as the zones of growth retardation of microorganisms are formed due to the diffusion of biologically active substances into a dense nutrient medium.It was found that extract No 1 had high activity and delayed the growth of Staphylococcus aureus ATCC 26923 to 22-23 mm. At the same time, this extract was maximum effective towards the representatives of gram-positive microflora, and reduced the activity of the gram negative microflora, the growth retardation zone in Escherichia coli ATCC 25922 and Proteus vulgaris ATCC 4636 is 16-17 mm. The smallest sensitivity among the studied strains was Pseudomonas aeruginosa ATCC 27853.Effect on pathogenic mushrooms, which was Candida albicans ATCC 885/653, was also sufficiently sensitive. When modifying the extract by increasing the amount of phenolic compounds and amino acids, we received a multi-directional action. Thus, the inclusion of arginine in the complex of phenolic compounds did not significantly affect the antimicrobial action. The inclusion of amino acid L-lysine to phenolic complex increased the antimicrobial and antifungal activity and slightly decreased the antimicrobial effect in relation to the representatives of gram-negative flora.Conclusions. 1) For the first time, extracts of S. officinalis in most have antimicrobial activity at the level of weakly active or active substances.2) The inclusion of L-lysine phenolic complex provided more pronounced antimicrobial effect on most strains in comparison with phenolic complex.3) Derivatives of S. officinalis extracts are promising objects for further study of anti-inflammatory activity as potential effective substances for the treatment and prevention of infectious intestinal diseases.